Outcomes of Patients with Newly Diagnosed Cardiac Myxoma: A Retrospective Multicentric Study. (6th February 2018) - Nehaj, Frantisek; Sokol, Juraj; Mokan, Michal; Jankovicova, Veronika; Kovar, Frantisek; Kubaskova, Marianna; Mizera, Stanislav; Mokan, Marian
Abstract : The patient database at the First Department of Internal Medicine in Martin, the Central Slovak Institute for Cardiac and Vascular Diseases in Banska Bystrica, and the National Slovak Institute of Cardiovascular Diseases in Bratislava was searched to identify patients with benign tumors of the heart seen during the 5-year period between 2011 and 2016. Forty-one patients with primary cardiac myxomas were identified and their medical records were reviewed for details pertaining to presenting symptoms, staging modalities, treatment approaches, and outcomes. Most of the studied patients were diagnosed with echocardiography (n = 35, 85%). The occurrence of the tumor was higher in the female population (n = 25, 61%). The most common presenting symptoms were dyspnoea (n = 17, 42%), chest pain (n = 3, 7%), or pain and paraesthesia of the limbs (n = 2, 5%). Acute embolic event due to embolization of tumor fragments resulted in cerebral stroke (n = 5, 12%). All patients were treated by resection. Only one comorbid patient died due to multiple-organ dysfunction syndrome two weeks after the resection. The most common postoperative complication was bleeding (n = 2, 5%) and infection (n = 2, 5%). The early diagnosis and appropriate treatment are often curative, with very low risk of recurrence. Postoperative survival is high.